Long-Term Results after Multilevel Fusion of the Cervical Spine and the Cervicothoracic Junction: To Bridge or Not To Bridge? - Scholz, Christoph; Klingler, Jan-Helge; Masalha, Waseem; Hohenhaus, Marc; Volz, Florian; Vasilikos, Ioannis; Roelz, Roland; Scheiwe, Christian; Hubbe, Ulrich (World neurosurgery, 2021)
For patients with multilevel degenerative cervical myelopathy, laminectomy and fusion are widely accepted techniques for ameliorating the disorder. However, the idea of whether one should bridge the cervicothoracic junction to prevent instrument failure or adjacent segment disease has been a subject of controversial discussion. In the present study, we compared the incidence of these complications and the revision rates in multilevel fusions extending to C7 or T1–T3. In the present single-center, retrospective cohort study, patients with multilevel degenerative cervical myelopathy treated with laminectomy and fusion to C7 or T1–T3 from 2004 to 2016 were included for evaluation. The primary outcome measure was radiologically proven complications at the most caudal level or the adjacent spinal fusion level. Laminectomy and multilevel fusion were performed in 84 patients. After applying the exclusion criteria, 20 patients with fusion to C7 (treated from 2004 to 2012; follow-up, 124.6 ± 10.6 months) and 38 patients with fusion to T1–T3 (treated from 2008 to 2016; follow-up, 58.2 ± 15.7 months) were evaluated. The incidence of complications at the most caudal or adjacent level of fusion was twice as high (P = 0.087; NS) in the C7 group (11 of 20; 55.0%) compared with the T1–T3 group (11 of 38; 28.9%). In the C7 group, 9 of the 20 patients (45.0%) had required revision surgery compared with 2 of 38 patients (5.3%) in the T1–T3 group (P = 0.001). We found that fewer revisions were necessary if the fusion had extended to the thoracic spine. Thus, we recommend bridging the cervicothoracic junction when fusion starts at C0–C3.